A Motivation-Based Typology of Road Cyclists in the Cape Town Cycle Tour, South Africa. Issue 3 (23rd March 2016) - Kruger, Martinette; Myburgh, Esmarie; Saayman, Melville
ABSTRACT: This research identified cyclists' main motives for participating in the Cape Town Cycle Tour, and segmented them accordingly. Six distinct motives were identified (in order of importance): commitment and event affiliation, lifestyle, achievement and challenge, escape and socialization, international standing of event, and skill mastery and group affiliation. On the basis of these motives, two distinct national cycling segments and one international segment were identified: Regulars, Devotees, and Beginners. The findings confirm that event cyclists should not be regarded as homogeneous and that the type of sport and the nature of the event significantly influence the type of participant.